2022
DOI: 10.1111/eea.13249
|View full text |Cite
|
Sign up to set email alerts
|

Estimating predation pressure in ecological studies: controlling bias imposed by using sentinel plasticine prey

Abstract: Sentinel plasticine prey has been increasingly used to estimate predation pressure. The use of plasticine prey may, however, bias the results, as this method was originally designed to account for predation by organisms that can visually recognize the shapes and colors of their prey. To evaluate the limitations of using sentinel plasticine prey, we compared predator attack rates between real prey – dead and live mealworms, Tenebrio molitor L. (Coleoptera: Tenebrionidae) – and plasticine models in a monsoonal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Concerns about using plasticine models for assessing predation risk, especially for measuring invertebrate predation, have been expressed in several publications (Greenop et al, 2019;Nimalrathna et al, 2023;Vet & Dicke, 1992;, but our study experimentally demonstrates the limitations and caveats of this method. We have shown (Table 1) that the use of plasticine prey models can lead to wrong conclusions about T A B L E 1 Overview of experiments and their results.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Concerns about using plasticine models for assessing predation risk, especially for measuring invertebrate predation, have been expressed in several publications (Greenop et al, 2019;Nimalrathna et al, 2023;Vet & Dicke, 1992;, but our study experimentally demonstrates the limitations and caveats of this method. We have shown (Table 1) that the use of plasticine prey models can lead to wrong conclusions about T A B L E 1 Overview of experiments and their results.…”
Section: Discussionmentioning
confidence: 75%
“…The importance for ants of being able to pick up prey is overlooked in most studies of ant predation on sentinel prey, because experimental prey, even when alive, are usually fixed to some surface (e.g., Drozdov a et al, 2013;Nimalrathna et al, 2023). We therefore conclude that plasticine models are badly suited for quantifying invertebrate predation because, at least in some habitats, some important groups of predators do not attack plasticine models.…”
Section: Invertebrate Predationmentioning
confidence: 90%
“…In the case of our predator assay, clay caterpillars are certainly of lower nutritional value to birds. Although the use of clay caterpillars is widespread, the method comes with explicit biases in that the lack of chemical and behavioral cues drives the underestimation of predation rates as compared with live sentinel prey (Nimalrathna et al, 2023; Zvereva & Kozlov, 2023). Even though the intensity of predation is likely underestimated in our study, we believe this method to be as informative of predator behavior as if using real prey, acknowledging that actual predation may be at a higher rate (Lövei & Ferrante, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some predators respond similarly to live and plasticine sentinel prey (Ferrante et al, 2017), but in general, attack rates on plasticine sentinels tend to be lower (Lövei & Ferrante, 2017). Two new studies have also found artificial prey can underestimate attacks by invertebrates more severely than those by vertebrates (Nimalrathna et al, 2023; Zvereva & Kozlov, 2022). Disparities between attack rates on live prey vs. artificial sentinels can also change strongly within a season and do so inconsistently depending on the predator group in question, leading to misleading conclusions about the relative importance of various predator groups.…”
Section: Discussionmentioning
confidence: 99%